Papa Francesco e la Chiesa degli Stati Uniti - Buttiglione, Rocco (La scuola cattolica, 2025)
The author traces the history of the Catholic Church and her members in the United States: from the initial suspicion of being un-American to the full inculturation, culminating with the Centesimus Annus of John Paul II, up to the request of a new equilibrium, especially following the election of Pope Francis. The analysis highlights the ongoing challenge for American Catholicism in rediscovering a new ‘outgoing’ identity. The Church of the United States is called today to a new mission: that of incarnating the universality of the christian message in a multi-polar world, thus knowing how to inhabit, stimulated by the pope’s leadership, the symphonic tensions which have always constituted Catholic unity.